The Effect of Education Regarding Gastritis Using Flip Sheet Media on Frequency of Irritant Eating and Stress Levels in Adolescents Suffering from Gastritis at SMAN 7 Samarinda - Muthmainnah Hasanuddin Usman; Kurniati Dwi Utami; Mustaming; Joko Cahyono (Journal of Educational Analytics, 2023)
Gastritis is an abnormality in the mucosal nerves resulting in inflammation which is commonly suffered by teenagers. Preliminary study results showed that several teenagers with a history of gastritis had a high frequency of eating irritants and high levels of stress. The aim of the research was to determine the effect of gastritis education using flip sheets on the frequency of eating irritants and stress levels. The research method is, Quasy Experiment Non-Equlvalent Control Group Design approach involving 50 teenagers, divided into 2 groups. The statistical analysis used is the Wilcoxon test and independent t-test. The results showed that 0.000<0.05 meant there was a significant difference in the frequency of irritant eating and stress levels between the experimental and control groups. In conclusion, gastritis education using flip sheets has an effect on eating frequency and stress levels in teenagers suffering from gastritis at SMAN 7 Samarinda.